2018
DOI: 10.1111/jeb.13294
|View full text |Cite
|
Sign up to set email alerts
|

Successful despite poor flight performance: range expansion is associated with enhanced exploratory behaviour and fast development

Abstract: Anthropogenic interference forces species to respond to changing environmental conditions. One possible response is dispersal and concomitant range shifts, allowing individuals to escape unfavourable conditions or to track the shifting climate niche. Range expansions depend on both dispersal capacity and the ability to establish populations beyond the former range. We here compare well-established core populations with recently established edge populations in the currently northward expanding butterfly Lycaena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 84 publications
(126 reference statements)
2
10
0
Order By: Relevance
“…For instance, we did not find differences between sexes, although a better flight performance in males has been shown for the study species in previous experiments (Reim et al. , b, see Fig. b for a non‐significant tendency).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…For instance, we did not find differences between sexes, although a better flight performance in males has been shown for the study species in previous experiments (Reim et al. , b, see Fig. b for a non‐significant tendency).…”
Section: Discussionsupporting
confidence: 43%
“…Third, flight performance was measured after the experiments on emigration propensity, which could have influenced the results obtained. For instance, we did not find differences between sexes, although a better flight performance in males has been shown for the study species in previous experiments (Reim et al 2018a, b, see Fig. 4b for a non-significant tendency).…”
Section: Study Limitationssupporting
confidence: 51%
“…Interestingly, experimental estimations of flight endurance do not reflect this. For example, some studies of Pieris brassicae reported higher flight endurance in females relative to males (Ducatez et al ., ; Reim et al ., ). Thus, the generally lower flight activity observed in females may not reflect weaker flight capacity, but could simply reflect behavioural adjustments to save energy.…”
Section: What Selective Factors Influence Flight and Associated Wing mentioning
confidence: 97%
“…Previous empirical range expansion studies have mainly focused on species with fast life histories (i.e. the classical r-strategists) [11,22,23]. Climate change-induced range shift, however, also concerns species on the other extreme of the pace-of-life continuum [24].…”
Section: Introductionmentioning
confidence: 99%